The Effect Of Tax Accounting Choice, Size And Multinational Company On Tax Aggresiveness: The Effect Of Tax Accounting Choice, Size And Multinational Company On Tax Aggresiveness - Muhammad Rinaldi; Melda Aulia Ramadhani (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study aims to analyze the variables of Tax Accounting Choices, Size and Multinational Company on Tax Aggressiveness. The sample used in this study was 28 Basic Industrial and Chemical Sector Manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 - 2022. Samples are taken by purposive random sampling using certain criteria. Tax Accounting Choices are measured by the dummy variable of choosing the depreciation method of fixed assets, while for Size is measured by the value of the Natural Logarithm (LN) of total assets. Multinational Company is measured using dummy variables where companies operating at the international level are given a score of 1 and 0 if the company is not operating international class. The results of this study show that Tax Accounting Choice and Multinational Company have no effect on Tax Aggresiveness. While the Size variable has a negative effect on Tax Aggresiveness.